The Correlations Between Measurement of Lung Diffusing Capacity for Carbon Monoxide and The Severity Group of Asthma Patients in Persahabatan Hospital Jakarta - Bulkis Natsir; Faisal Yunus; Triya Damayanti (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Introduction: Airway remodeling in asthma which involve small airway can affect until alveoli and cause abnormalities in the lung parenchyma. This study tries to find lung parenchymal abnormalities in patients with asthma through the examination diffusion capacity with a single breath DLCO method.Methods: A cross-sectional study by dividing asthma based on the degree of severity into two major groups, namely mild asthma (intermittent and mild persistent) and severe (persistent moderate and severe). The amount of each group is 31 subjects and 29 subjects, which are taken consecutively from stable asthma patients without comorbid who are seeking treatment in Persahabatan Hospital in December 2015 - May 2016.Results: The average value of DLCO /predictions in mild asthma group is 92,74 ± 15,70% and decreased in the severe asthma group is 77,45 ± 16,78%. Some spirometry value showed significant positive correlation with the value of DLCO/prediction, namely: FVC/prediction, FEV1 /prediction and FEF25-75 % / prediction with p < 0.05. Correlation analysis showed FVC/prediction could dramatically affect the diffusion capacity of asthmatic patients. There is a significant relationship between abnormalities in lung function (p=0,004) and severity of asthma (p=0.000) with a corresponding decrease DLCO / prediction (DLCO/ prediction ≤75 %).Conclusion: The severity of asthma has a relationship with the diffusion capacity of the lungs, increased severity will decrease the diffusion capacity in asthma patients. Decreasing diffusion capacity showed that abnormalities in asthma not only occur in the respiratory tract but also in the lung parenchyma.